Outer Membrane Changes in a Toluene-Sensitive Mutant of Toluene-Tolerant Pseudomonas putida IH-2000 - Kobayashi, Hideki (American Society for Microbiology, 1999)
We isolated a toluene-sensitive mutant, named mutant No. 32, which showed unchanged antibiotic resistance levels, from toluene-tolerant Pseudomonas putida IH-2000 by transposon mutagenesis with Tn5. The gene disrupted by insertion of Tn5 was identified as cyoC, which is one of the subunits of cytochrome o. The membrane protein, phospholipid, and lipopolysaccharide (LPS) of IH-2000 and that of mutant No. 32 were examined and compared. Some of the outer membrane proteins showed a decrease in mutant No. 32. The fatty acid components of LPS were found to be dodecanoic acid, 2-hydroxydodecanoic acid, 3-hydroxydodecanoic acid, and 3-hydroxydecanoic acid in both IH-2000 and No. 32; however, the relative proportions of these components differed in the two strains. Furthermore, cell surface hydrophobicity was increased in No. 32. These data suggest that mutation of cyoC caused the decrease in outer membrane proteins and the changing fatty acid composition of LPS. These changes in the outer membrane would cause an increase in cell surface hydrophobicity, and mutant No. 32 is considered to be sensitive to toluene.